2021
DOI: 10.1158/2159-8290.cd-21-0410
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Functional Precision Medicine Tumor Board for Acute Myeloid Leukemia

Abstract: We generated ex vivo drug-response and multiomics profiling data for a prospective series of 252 samples from 186 patients with acute myeloid leukemia (AML). A functional precision medicine tumor board (FPMTB) integrated clinical, molecular, and functional data for application in clinical treatment decisions. Actionable drugs were found for 97% of patients with AML, and the recommendations were clinically implemented in 37 relapsed or refractory patients. We report a 59% objective response rate for the individ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
124
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(125 citation statements)
references
References 50 publications
(76 reference statements)
1
124
0
Order By: Relevance
“…This analysis revealed PEAR1 to perform equivalently to LSC17 both in the young subset and across all age groups (Figure S6). Finally, to validate the prognostic significance of PEAR1 using independent patient cohorts, we examined the capacity of PEAR1 expression to stratify overall survival using a dataset from Malani and coworkers as well as from The Cancer Genome Atlas (TCGA) (Cancer Genome Atlas Research et al, 2013;Malani et al, 2022). We found that elevated PEAR1 expression conferred shortened overall survival in a strongly significant manner in both datasets (Figures S7A and S7B).…”
Section: Determinants Of Clinical Outcomementioning
confidence: 93%
“…This analysis revealed PEAR1 to perform equivalently to LSC17 both in the young subset and across all age groups (Figure S6). Finally, to validate the prognostic significance of PEAR1 using independent patient cohorts, we examined the capacity of PEAR1 expression to stratify overall survival using a dataset from Malani and coworkers as well as from The Cancer Genome Atlas (TCGA) (Cancer Genome Atlas Research et al, 2013;Malani et al, 2022). We found that elevated PEAR1 expression conferred shortened overall survival in a strongly significant manner in both datasets (Figures S7A and S7B).…”
Section: Determinants Of Clinical Outcomementioning
confidence: 93%
“…These systems biology data sets can readily be generated from both prospective fresh samples and viably frozen biobanked samples with good technological success rates. In one of the recent studies on AML, actionable drugs were found for 97% of the 252 included patient samples [123]. The same study also suggested individually tailored therapies for 37 relapsed or refractory AML patients and reported that 59% of the patients had objective responses, which are praising for the added value of the FPM approach.…”
Section: Fpm As a Complement To Comprehensive Molecular Profilingmentioning
confidence: 96%
“…To exclude general toxicity and to provide for disease selectivity, calculation of the difference to a control sample, such as healthy bone marrow, is often included in the hit scoring [117,121]. Viability-based FPM has been used to profile drug responses and to create large cohorts of leukaemia cases often including molecular omic profiling [34,122,123]. These systems biology data sets can readily be generated from both prospective fresh samples and viably frozen biobanked samples with good technological success rates.…”
Section: Fpm As a Complement To Comprehensive Molecular Profilingmentioning
confidence: 99%
“…2 However, risk stratifications that included clinical and biological information, and are under discussion. 16 Functional analyses of drug sensitivity and signaling responses are suggested, 14,[17][18][19] but based on our previous observations of protein and gene expression hours after start of chemotherapy, 11,12 we hypothesize that early chemotherapy-induced alterations in intracellular signaling networks may be a more accurate predictor of long-term therapy response. Here, we have employed mass cytometry to investigate intracellular signaling networks in peripheral blood (PB) samples from 32 newly diagnosed AML patients during the first 24 hours of standardized induction chemotherapy.…”
Section: Introductionmentioning
confidence: 99%